2006
DOI: 10.1103/physrevlett.96.111101
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Evolutions of Orbiting Black-Hole Binaries without Excision

Abstract: We present a new algorithm for evolving orbiting black-hole binaries that does not require excision or a corotating shift. Our algorithm is based on a novel technique to handle the singular puncture conformal factor. This system, based on the BSSN formulation of Einstein's equations, when used with a 'pre-collapsed' initial lapse, is non-singular at the start of the evolution, and remains nonsingular and stable provided that a good choice is made for the gauge. As a test case, we use this technique to fully ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
1,907
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,312 publications
(1,948 citation statements)
references
References 22 publications
34
1,907
1
6
Order By: Relevance
“…For the late inspiral, merger and ringdown phases [8], the PN models are not applicable and it is mandatory to use the numerical-relativity (NR) simulations based on the breakthrough [21,22,23] (see also [24,25,26,27,28,29]) as well as other analytical treatments combined with NR waveforms, including effective-one-body formalism [30,31,32,33,34,35,36,37] and phenomenological models [38,39,40,41,42,43,44]. The BBH waveform models have been further improved over the years and many applications to detection have already followed.…”
Section: Goals and Motivationsmentioning
confidence: 99%
“…For the late inspiral, merger and ringdown phases [8], the PN models are not applicable and it is mandatory to use the numerical-relativity (NR) simulations based on the breakthrough [21,22,23] (see also [24,25,26,27,28,29]) as well as other analytical treatments combined with NR waveforms, including effective-one-body formalism [30,31,32,33,34,35,36,37] and phenomenological models [38,39,40,41,42,43,44]. The BBH waveform models have been further improved over the years and many applications to detection have already followed.…”
Section: Goals and Motivationsmentioning
confidence: 99%
“…Several gravitational wave detectors [1][2][3] have now achieved a high enough level of sensitivity that the first astrophysical observations are expected to occur within the next few years. The numerical relativity community has also matured to the point that several groups are now computing model gravitational waveforms for the inspiral and merger of black hole and neutron star binary systems [4][5][6][7][8][9][10][11][12][13]. Beyond the pioneering work of Mark Miller [14] and Stephen Fairhurst [15], however, little effort has gone into thinking about the question of how accurate these model waveforms need to be.…”
Section: Introductionmentioning
confidence: 99%
“…Early estimates of these gravitational recoils or "kicks" using post-Newtonian (PN) techniques [4] and black-hole perturbation theory [5] suggested that they would not exceed several hundred km/s in magnitude. More recently, progress in numerical relativity (NR) [6][7][8] has allowed relativists to simulate the mergers of highly spinning, comparable-mass black holes. For non-spinning binaries, ensuing studies identified a maximum recoil of 175 km/s [9].…”
Section: Introductionmentioning
confidence: 99%